Clinical experience of primary subcutaneous mycoses in Shanghai: a retrospective analysis - Yu, Qian; Li, Lulu; Wang, Yuanyuan; Gao, Zhiqin; Liu, Siyu; Tan, Jingwen; Liu, Xiaoping; Li, Wei; Yang, Lianjuan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPrimary subcutaneous mycoses are a heterogeneous group of fungal infections caused by pathogenic or opportunistic organisms. In recent years, cases have steadily increased in Shanghai, an area where the disease was previously uncommon. This study aimed to summarize clinical experiences with primary subcutaneous mycoses in Shanghai, to optimize their management.MethodA retrospective analysis was conducted at Shanghai Dermatology Hospital from January 2018 to March 2023 and enrolled 33 patients with confirmed primary subcutaneous mycoses. Their medical histories, clinical features, histopathological findings, etiological characteristics, drug sensitivity tests, therapeutic regimens, and follow-up data were recorded.ResultsIdentification of pathogens from skin tissue cultures revealed distinct colonial morphologies across diverse mycological species. The isolates included yeast (45.5%), mold (30.3%), and dimorphic fungi (24.2%). The most common species were C. parapsilosis (n = 8, 24.2%), T. rubrum (n = 5, 15.2%), and S. schenckii (n = 8, 24.2%). Thirty-two patients received systemic antifungal treatment based on the results of the drug sensitivity test, whereas one patient was treated with complete surgical resection, owing to a single plaque. Post-treatment surveillance was important for the effective management of the condition.ConclusionThis study highlights the considerable diversity among fungal species implicated in primary cutaneous mycoses and underscores the complexities involved in their accurate diagnosis and management. Correcting unhealthy lifestyles, boosting immunity, and completely removing and avoiding re-exposure to the pathogenic fungi can effectively reduce the risk of relapse in primary subcutaneous mycoses. Our findings provide valuable insights into primary subcutaneous mycoses and may contribute to improved patient prognoses.